Synthesis and Characterization of Zinc(II) and Cadmium(II) Complexes of N,N'-ethylene-bis(3-carboxypropenamide) - Viswanathan, M. (Asian Journal of Chemistry, 2016)
Complexes of Zn(II) and Cd(II) with a tetradentate ligand N,N'-etyhlene-bis(3-carboxypropenamide) (EBCPH2) have been synthesized and characterized by elemental analysis, conductance, thermal, magnetic, infrared and X-ray powder diffraction studies. The complexes have been assigned the formula [M(EBCP)(H2O2] where M = Zn or Cd. These complexes have octahedral geometry.